THE CHALLENGES OF BIOETHICS IN ASIA: A NATURAL LAW PERSPECTIVE - Tham, S Joseph (Asian Horizons, 2013)
Asia is not a homogenous entity, its vast geography and cultural, religious and ethical traditions embrace Confucianism, Hinduism, Buddhism, Islam and Christianity. The challenges facing bioethics in Asia are manifold. Bioethics began in the West as a discipline that has developed over the past forty years. Even though its roots are in the Christian moral tradition, bioethics today is predominantly secular.